Overcoming the current issues surrounding device leads: reducing the complications during extraction. (3rd June 2017) - Bongiorni, Maria Grazia; Segreti, Luca; Di Cori, Andrea; Zucchelli, Giulio; Paperini, Luca; Viani, Stefano; Soldati, Ezio
ABSTRACT: Introduction : The implantation rate of cardiac implantable electronic devices has consistently increased in the last 20 years, as have the related complication rates. The most relevant issue is the removal of pacing and implantable cardioverter defibrillator (ICD) leads, which a few months after implantation tend to develop intravascular fibrosis, often making extraction a challenging and risky procedure. Areas covered : The transvenous lead extraction (TLE) scenario is constantly evolving. TLE is a key procedure in lead management strategies. Many efforts have been made to develop new TLE approaches and techniques allowing a safe and effective procedure for patients. The increasing rate of cardiac implantable electronic device (CIED) implantations and of CIED related complications highlight the importance of TLE. Lead related- and patient-related factors may change the future of extractions. We review the current status of TLE, focusing on the strategies available to perform the optimal procedure in the right patient and reducing procedure related complications. Expert commentary : Understanding the importance of an accurate TLE risk stratification is mandatory to optimize the procedural risk-to-benefits ratio. The use of adequate tools, techniques and approaches, and appropriate training are cornerstones for the achievement of safer procedures.